Synthesis, Structure, Reactivity, and Intramolecular Donor-Acceptor Interactions in a Phosphinoferrocene Stibine and Its Corresponding Phosphine Chalcogenides and Stiboranes - Schulz, Jiří; Antala, Jakub; Rezazgui, David; Císařová, Ivana; Štěpnička, Petr (Inorganic chemistry, 2023)
Ferrocene-based phosphines equipped with additional functional groups are versatile ligands for coordination chemistry and catalysis. This contribution describes a new compound of this type, combining phosphine and stibine groups at the ferrocene backbone, viz. 1-(diphenylphosphino)-1'-(diphenylstibino)ferrocene (1). Phosphinostibine 1 and the corresponding P-chalcogenide derivatives Ph2P(E)fcSbPh2 (1E, fc = ferrocene-1,1'-diyl, E = O, S, Se) were synthesized and further converted to the corresponding stiboranes Ph2P(E)fcSb(O2C6Cl4)Ph2 (6 and 6E) by oxidation with o-chloranil. All compounds were characterized by spectroscopic methods, X-ray diffraction analysis, cyclic voltammetry, and theoretical methods. Both NMR spectroscopy and DFT calculations confirmed the presence of P → Sb and P═O → Sb donor-acceptor interactions in 6 and 6O, triggered by the oxidation of the stibine moiety into Lewis acidic stiborane. The corresponding interactions in 6S and 6Se were of the same type but significantly weaker. A coordination study with AuCl as the model metal fragment revealed that the phosphine group acts as the "primary" coordination site, in line with its higher basicity. The obtained Au(I) complexes were applied as catalysts in the Au-catalyzed cyclization of N-propargylbenzamide and in the oxidative [2 + 2 + 1] cyclization of ethynylbenzene with acetonitrile and pyridine N-oxides. The catalytic results showed that the stibine complexes had worse catalytic performance than their phosphine counterparts, most likely due to the formation of weaker coordination bonds and hence poorer stabilization of the active metal species. Nevertheless, the stibine moiety could be used to fine-tune the properties of the ligated metal center by changing the oxidation state or substituents at the "remote" Sb atom.